A Critical Insight into the Character of Cleopatra in Shakespeare’s tragedy; Antony and Cleopatra where She is both a victim of male domination as well as a subverter of male authority - Dr. Inayat Chaudhary (The Creative Launcher, 2018)
The paper attempts to demonstrate the character of Cleopatra from Shakespeare’s work of tragedy –Antony and Cleopatra. Efforts are made to depict the reversal of gender positions as with the progression of the play the woman character of Cleopatra becomes powerful and masculine whereas Antony comes to represent more feminine aspects. The renaissance period’s societal setup also echoes in the plays setup as women in the public sphere are a reason of mistrust, uneasiness and anxiety. The thorough critical approach of the character of Cleopatra only makes her more human with all her flaws imperfections. Further, feminist and post colonial approaches are also discussed in the paper to provide an in-depth and justified study of her personality. Hence, Cleopatra becomes a representative of women empowerment by playing an active role in questioning the societal norms and values. Thereby, making her one of the most remembered characters of Shakespeare’s plays.